Pleomorphic adenoma of deep lobe of parotid: A rare pediatric tumor - Sandesh V. Parelkar; Rujuta Shah; Natasha L. Vageriya; Beejal V. Sanghvi; Bhupesh Paradkar; Satej Mhaskar (Elsevier, 2016)
Salivary gland neoplasms are extremely rare in children and comprise less than 1% of all pediatric neoplasms. Benign neoplasms account for 60% of these salivary tumors in children. They are most commonly vascular in origin with parotid glands being affected commonly. Pleomorphic adenoma is common in adults; it is extremely rare in pediatric age group. We report a 9 year old girl with a parotid region swelling; suspected to be a pleomorphic adenoma of the superficial lobe of parotid. However, it was arising from the deep lobe & hence was managed with an enucleation of the tumor with no evidence of recurrence after 3 years of follow up.